(untitled) (Singapore, 2001)
V.N. Gribov, one of the founders of modern particle physics, shaped our understanding of QCD as the microscopic dynamics of hadrons. This volume collects his papers on quark confinement, showing the road he followed to arrive at the theory and formulating the theory itself. It begins with papers providing a physical explanation of asymptotic freedom based on the phenomenon of anti-screening and demonstrating the inconsistency of the standard perturbative treatment of the gluon fields (Gribov copies, Gribov horizon). It continues with papers presenting the Gribov theory according to which confinement of colour is determined by the existence of practically massless quarks. The last two papers conclude Gribov's 20-year-long study of the problem; QCD is formulated as a quantum field theory containing both perturbative and nonperturbative phenomena, and the confinement is based on the supercritical binding of light quarks.
Keywords: Quark confinement,Thu gom Quark